Answer:
The answer is: ![2x^2-7x-2](https://tex.z-dn.net/?f=2x%5E2-7x-2)
Step-by-step explanation:
we are asked to subtract
from ![2x^2-11](https://tex.z-dn.net/?f=2x%5E2-11)
so,
.
Hence the desired result is:
.
So we have lengths a and b and are given:
2a+2b = 66 => a+b = 33 => a= 33-b
a*b = 272
plug in one into the other:
(33-b)b = 272 => -b^2 +33b - 272 = 0
Can be factored as (b-16)(b-17) = 0, if you don't "see" this immediately, use the well known abc formula to find b.
So a=16 and b=17 or vice versa.
Answer:
3/6
Step-by-step explanation:
no idea if its right
Answer:12
Step-by-step explanation:
Because I’m right anywhere
If you are doing a multi step question that looks something like this: 23+(4)-4 or longer. You will have to use a formula called BEDMAS. It stands for brackets, exponents( which are little numbers on top of a number), then you deal with division, multiplication, addition, and subtraction. You will have to solve your equation in this order. If you don’t you will get another, answer.